The Extremal Permanental Sum for a Quasi-Tree Graph - Tingzeng Wu; Huazhong Lü (Complexity)
Let G be a graph and A(G) the adjacency matrix of G. The permanent of matrix (xI-A(G)) is called the permanental polynomial of G. The permanental sum of G is the sum of the absolute values of the coefficients of permanental polynomial of G. Computing the permanental sum is #p-complete. In this note, we prove the maximum value and the minimum value of permanental sum of quasi-tree graphs. And the corresponding extremal graphs are also determined. Furthermore,we also determine the graphs with the minimum permanental sum among quasi-tree graphs of order n and size m, where n-1≤m≤2n-3.